Confinement Assembly: Self‐Assembly of Diblock Molecular Polymer Brushes in the Spherical Confinement of Nanoemulsion Droplets. Issue 19 (5th October 2018) - Steinhaus, Andrea; Pelras, Théophile; Chakroun, Ramzi; Gröschel, André H.; Müllner, Markus
Abstract : Back Cover : Polymer self‐assembly under confinement conditions has emerged as a versatile avenue to design polymer particles with complex internal morphologies. In article number1800177, André H. Gröschel, Markus Müllner, and co‐workers self‐assemble diblock molecular polymer brushes under confinement in drying emulsion droplets to form uniform microparticles with highly ordered internal structures, such as axiallystacked lamellar morphologies.